Öğrencilerin atom ve atomun enerji seviyeleri ile ilgili görüşleri - Hanoğlu, Seda (My University, 2004)
In this study, determination of students' ideas about Atom and Atom' s Energy Levels subject, one of the fundamental subject of physics, has aimed. In the study individual interviews, Analogy and Demonstration methods have used. Data has collected with questionnaire and individual interviews . Questionnaire involves three subjects. These subjects are atom' s structure, atom models and atom's energy levels. For this aim, Questionnaire Form containing 8 open - ended questions based on this subjects were applied to 85 students attending Science High School and University. According to answers taken from Questionnaire Form, student mental models were to be constructed. Also individual interviews have made with 6 students who determined according to answers taken from Questionnaire Form. In these interviews, activities related each subjects in the questionnaire has added. These activities have used to collect information about how to constructed concepts that learned in mind. During the evaluation of research data, induction analysis has used for to determine students' ideas. Also, individual interviews have recorded with the permission of interviewed person and analyzed with qualitative data analysis. In the result part of this research, answers of questionnaire have shown as tables and graphs. Students' ideas that related atom and atom's energy levels have determined, then these ideas have analyzed with interviews and resulting of this analysises, suggestions have presented about teaching atom subjects to students.

Bu çalışma ile fiziğin temel konularından biri olan Atom ve Atomun Enerji Seviyeleri konusu ile ilgili öğrencilerin fikirlerinin tespit edilmesi ve bu fikirlerin ayrıntılarının, Benzetme ve Gösteri yöntemleri kullanılarak yapılan bireysel görüşme sürecinde incelenmesi amaçlanmıştır. Veriler anket ve bireysel görüşme yöntemleri kullanılarak toplanmıştır. Anket soruları üç konuyu içermektedir. Bu konular ; atomun yapısı, atom modelleri ve atomun enerji seviyeleridir. Bu amaçla bir Fen Lisesi ve bir Üniversitede okuyan 85 öğrenciye bu konularla ilgili 8 açık uçlu sorudan oluşan Anket Formu uygulanmıştır. Anket Formundan alınan sonuçlara göre öğrenci zihinsel modelleri oluşturulmuştur. Ayrıca Anket Formu sonuçlarına göre belirlenen 6 öğrenci ile bireysel görüşmeler yapılmıştır. Görüşmede Anket Formundaki üç konu ile ilgili sorulara ek olarak her konu ile ilgili birer etkinliği de yer verilmiştir. Bu etkinlikler öğrencilerin öğrendikleri kavramları zihinlerinde nasıl yapılandırdıkları hakkında bilgi edinmek için kullanılmıştır. Araştırma verilerinin değerlendirilmesi aşamasında, öğrencilerin fikirlerini belirlemek için kullanılan anketin analizinde tümevarımsal analiz metodu kullanılmıştır. Ayrıca yapılan bireysel görüşmeler görüşülen kişinin izni ile kaydedilmiş ve nitel veri analizi ile incelenmiştir. Araştırma sonucunda anket sorularının yanıtları tablolar ve grafikler halinde gösterilmiştir. Öğrencilerin atom ve atomun enerji seviyeleri hakkındaki fikirleri tespit edilmiş, yapılan görüşmelerle bu fikirlerin ayrıntılarına inilmiş ve bunun sonucunda atom konusunun öğrencilere aktarımı ile ilgili öneriler sunulmuştur.
Keywords: Atom; Eğitim; Fizik Öğretmenliği; Müfredat; Orta öğretim